PERENCANAAN ULANG PERKUATAN STRUKTUR DERMAGA MENGGUNAKAN PONDASI TIANG PANCANG DENGAN VARIASI DIAMETER - Clarissa Rahma Anisadila; Herry Widhiarto; Laily Endah Fatmawati (LPPM Universitas Abdurrab, 2023)
The wharf is one of the supporting facilities for the process of loading and unloading goods on ships. For services for long-term ships and loads caused by the process of loading and unloading ships, the safety of the wharf needs to be improved by strengthening the foundation. Berlian Pier uses a steel pile foundation with a diameter of 1.016 m and a length of 32 m. This study used the Meyerhoff method to calculate the bearing capacity of the piles and N-SPT data for the Reinforcement of Wharf Structures Using Diameter Variations at Berlian Surabaya Pier. Based on the re-planning that has been done, it is concluded that a diameter of 1.00 m and a length of 32 m obtains a single pile bearing capacity of 8164 Tons, shear resistance of 28120.4 Tons, axial bearing capacity of 8345.42 Tons. Immediate settlement of 38.551 mm, annual settlement of 00,0201 mm, long-term settlement of 0,193 mm, and total settlement of 48,050 mm. Keywords: Variation Diameter, Carrying Capacity, Settlement